2021
DOI: 10.1002/er.6552
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling analysis of thermal runaway for LiNi 0 . 5 Mn 0 . 3 Co 0 . 2 O

Abstract: Summary The nickel‐rich lithium‐ion batteries (LIBs) are widely used as the energy source of new energy vehicles. But the relatively poor safety performance results in serious accidents, which attracts more and more attention of researchers. In this study, the thermal runaway (TR) features of a pouch cell consisted of LiNi0.5Mn0.3Co0.2O2/graphite are investigated by an extended volume‐accelerating rate calorimeter combined with resistance monitoring, voltage monitoring, and video imaging technologies. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…2), respectively, and the (d T /d t ) max was 84.98 °C min –1 . Self-heat rate is the most essential data needed for evaluating runaway hazards of LIBs under thermal failure . The (d T /d t ) max did not exceed 100 °C min –1 for both sets of experiments when the SOC of the battery was 25%, so T cr was not monitored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), respectively, and the (d T /d t ) max was 84.98 °C min –1 . Self-heat rate is the most essential data needed for evaluating runaway hazards of LIBs under thermal failure . The (d T /d t ) max did not exceed 100 °C min –1 for both sets of experiments when the SOC of the battery was 25%, so T cr was not monitored.…”
Section: Resultsmentioning
confidence: 99%
“…Self-heat rate is the most essential data needed for evaluating runaway hazards of LIBs under thermal failure. 33 The (dT/ dt) max did not exceed 100 °C min −1 for both sets of experiments when the SOC of the battery was 25%, so T cr was not monitored. Compared to SOC = 0%, T onset was lower and both T max and (dT/dt) max reached were higher when the battery SOC was 25%.…”
Section: Thermal Runaway Of 0% Socmentioning
confidence: 99%
“…The highest temperature recorded at this moment was at No. The experimental data and phenomena showed that the TR triggered by the surface heat source of the battery is similar to the adiabatic TR process [13]. As the temperature increases, the decomposition of the SEI on the negative electrode surface occurs, and a large amount of flammable and explosive gas is generated by the reaction between the negative electrode and the electrolyte, causing an increase in the internal pressure of the battery [14].…”
Section: Temperature and Voltage Characteristicsmentioning
confidence: 88%
“…The cell depressurizes in a relatively mild and stable manner. As the temperature continues to rise, the electrolyte will evaporate and overflow through the breach [13]. During the test, the erupting flammable and explosive gases served as the fuel, the oxygen provided by the external environment served as the oxidizer, and the splashing sparks served as the ignition source.…”
Section: Temperature and Voltage Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation